2022
DOI: 10.1111/opec.12232
|View full text |Cite
|
Sign up to set email alerts
|

Does overseas eco‐friendly innovation collaboration matter for environmental quality sustainability in India?

Abstract: The nexus between technological innovations and environmental quality has been much discussed in the field of energy economics and policy. However, the role of overseas eco-friendly innovation collaboration on environmental quality in India remains unaddressed. In such a line, our study raises the question of whether overseas eco-friendly innovation collaboration and total technological innovations collaboration are important towards health protection of the natural environment in India. This motivates us to s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 15 publications
(14 citation statements)
references
References 95 publications
1
13
0
Order By: Relevance
“…(2020) for Pakistan, Kais and Sami (2016) for the panel of fifty-eight countries, Usman et al . (2022b) for eight Arctic countries and Villanthenkodath and Mahalik (2022) for India. However, Mahalik et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…(2020) for Pakistan, Kais and Sami (2016) for the panel of fifty-eight countries, Usman et al . (2022b) for eight Arctic countries and Villanthenkodath and Mahalik (2022) for India. However, Mahalik et al .…”
Section: Literature Reviewmentioning
confidence: 99%
“…Besides, we suggest that emphasis should be given to public transport (i.e. train), cycle-riding and walking-habits mindsets of the tourists visiting many places, which can bring India's sustainable tourism and green economic growth in long run (Villanthenkodath and Mahalik, 2022).…”
Section: Results Discussion Of Ardl Modelmentioning
confidence: 99%
“…Moreover, it requires a more significant change in the living style of tourists in India. The attitude and perception of tourists towards effective dustbin use, cycle-riding and walking habits should be enhanced for the cleanness of the natural environment in India (Villanthenkodath and Mahalik, 2022). Finally, we suggest that growth policy in India targeting the short-term benefits of tourism growth generates irreversible and negative impact on the natural environment and destroys the basis of tourism built.…”
Section: Conclusion and Policy Implicationsmentioning
confidence: 99%
“…In the Indian context, (Villanthenkodath & Mahalik, 2022a) explore the role of overseas eco‐friendly technology collaboration on environmental quality in India. The study found that overseas eco‐friendly technology collaboration promotes environmental quality along with overseas total technology collaboration by reducing CO 2 emissions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…A serious concern about human well‐being, development and even survival has been posed by the unhealthy outcomes emanating from the regular changes in global climate conditions (Çetin et al, 2022; Demir et al, 2022; Magazzino et al, 2023). At this juncture, it is believed that the countries (companies) at the macro‐level (micro‐level) often neglect the environmental, humanitarian, and social aspects of development in the pursuit of economic development (Villanthenkodath & Mahalik, 2022a). Such negligence led to air pollution, thereby fostering climate change and global warming.…”
Section: Introductionmentioning
confidence: 99%